Curriculum evaluation in tourism education: Assessing the fulfillment of OBE principles - Rosita Rosita; Rudi Susilana; Rusman Rusman; Lina Rosliana (Graduate School, Universitas Negeri Yogyakarta in cooperation with Himpunan Evaluasi Pendidikan Indonesia (HEPI) Yogyakarta, 2025)
The shift toward Outcome-Based Education (OBE) in higher education requires tourism programs to conduct systematic curriculum evaluations to ensure relevance to evolving societal needs. This study evaluates the fulfillment of OBE principles in the Resort and Leisure Management (MRL) Program using the Stufflebeam’s CIPP (Context, Input, Process, Product) model. The evaluation analyzed the program’s curriculum document, 30 lesson plans, observed 18 courses, and conducted interviews and FGDs with lecturers, students, and program leaders. Context evaluation findings indicate that 9 of 10 PLOs lack measurable performance demonstrations, with less than half of CLOs consistently aligned with PLOs. Input evaluation supports the feasibility of a redesigned backward curriculum structure, while process evaluation highlights implementation gaps, particularly the predominance of lecture-based teaching, underutilization of digital learning systems, and administrative challenges in applying criteria-based assessments. Product evaluation confirms that although the curriculum is structurally OBE-compliant, its practical enactment does not yet guarantee authentic demonstration of graduate competencies. The study contributes empirical evidence showing the gap between curriculum documentation and instructional reality in tourism education. It also demonstrates the utility of the CIPP model as a system-oriented approach for improving OBE implementation.